Sense of smell in chronic rhinosinusitis: A multicentric study on 811 patients - Macchi, Alberto; Giorli, Alessia; Cantone, Elena; Carlotta Pipolo, Giorgia; Arnone, Flavio; Barbone, Umberto; Bertazzoni, Giacomo; Bianchini, Chiara; Ciofalo, Andrea; Cipolla, Federica; De Massimi, Alessio; De Vita, Carla; et al. (Frontiers in Allergy, 2023)
Introduction The impairment of the sense of smell is often related to chronic rhinosinusitis (CRS) with or without nasal polyps (CRSwNP, CRSsNP). CRSwNP is a frequent condition that drastically worsens the quality of life of those affected; it has a higher prevalence than CRSsNP. CRSwNP patients experience severe loss of smell with earlier presentation and are more likely to experience recurrence of their symptoms, often requiring revision surgery. Methods The present study performed a multicentric data collection, enrolling 811 patients with CRS divided according to the inflammatory endotype (Type 2 and non-Type 2). All patients were referred for nasal endoscopy for the assessment of nasal polyposis using nasal polyp score (NPS); Sniffin’ Sticks olfactory test were performed to measure olfactory function, and SNOT-22 (22-item sinonasal outcome test) questionnaire was used to assess patients’ quality of life; allergic status was evaluated with skin prick test and nasal cytology completed the evaluation when available. Results Data showed that Type 2 inflammation is more common than non-type 2 (656 patients versus 155) and patients suffer from worse quality of life and nasal polyp score. Moreover, 86.1% of patients with Type 2 CRSwNP were affected by a dysfunction of the sense of smell while it involved a lesser percentage of non-Type 2 patients. Indeed, these data give us new information about type-2 inflammation patients’ characteristics. Discussion The present study confirms that olfactory function weights on patients’ QoL and it represents an important therapeutic goal that can also improve patients’ compliance when achieved. In a future – and present – perspective of rhinological precision medicine, an impairment of the sense of smell could help the clinician to characterize patients better and to choose the best treatment available.